The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/2175-7860200051787901
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia da madeira de quatro espécies do gênero Miconia Ruiz & Pavón (Melastomataceae)

Abstract: RESUMONeste trabalho faz-se a descrição anatômica das madeiras de Miconia cabussu Hoehne, Miconia cinnamomifolia (DC.) Naudin, Miconia rigidiuscula Cogn. e Miconia sellowiana Naudin. As quatro espécies apresentam camadas de crescimento distintas; vasos solitários e em múltiplos; placas de perfuração simples; pontoações intervasculares pequenas, alternas e ornamentadas; parênquima axial paratraqueal escasso; raios integrados por células predominantemente quadradas e eretas; fibras semelhantes a parênquima, sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…; Ter Welle andKoek-Noorman 1981;Medeiros and Morretes 1994;Marcon and Costa 2000;Sonsin et al 2014;Silva et al 2015).However, in this study we observed the occurrence of trabeculae in vessel elements, and Alaccumulation in septa of fibers, in the G-layer of the gelatinous fibre walls, in the vacuole of ray cells, in the cambial cell walls, and in the walls of immature vessel elements. These features constitute new observations for Melastomataceae species.…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…; Ter Welle andKoek-Noorman 1981;Medeiros and Morretes 1994;Marcon and Costa 2000;Sonsin et al 2014;Silva et al 2015).However, in this study we observed the occurrence of trabeculae in vessel elements, and Alaccumulation in septa of fibers, in the G-layer of the gelatinous fibre walls, in the vacuole of ray cells, in the cambial cell walls, and in the walls of immature vessel elements. These features constitute new observations for Melastomataceae species.…”
contrasting
confidence: 47%
“…We believe that the absence of growth rings in R. dichotoma plants that grow in a swampy soil site might be related to the constant water availability in the soil while the fluctuation of water availability in the soil where the other species grow would reflect in growth markers in the wood. Melastomataceae species (Détienne and Jacquet 1983, Marcon and Costa 2000, Sonsin et al 2014, Silva et al 2015. The small amount of axial parenchyma and the higher amount of the parenchyma-like fibers rich in starch grains in the studied species support the hypothesis that the parenchyma-like characteristics in fibers might represent a way in which a wood ground tissue functioning like that of parenchyma can be achieved (Spackman andSwamy 1949, Carlquist 2001).…”
Section: Discussionmentioning
confidence: 54%
“…Melastomataceae is one of the main families of neotropical flora, with about 5,000 species belonging to 185 genera and 11 tribes. The interest in these plants stems from its eye-catching flowers; in Brazil, Miconia, the largest genus of the Melastomataceae family, is represented by about 250 ornamental species (Martins et al 1996, Marcon & Costa 2000. It is native to the forests of Central and South America extending from southern Mexico, in the north, toward the south through Guatemala, British Honduras, Nicaragua, Costa Rica, Panama, Colombia, Ecuador, Peru, Bolivia, Brazil, Paraguay, and northern Argentina.…”
Section: The Genus Miconia: a Natural Source Of Biologically Active Smentioning
confidence: 99%
“…The interest in these plants stems from its eye-catching flowers; in Brazil, Miconia, the largest genus of the Melastomataceae family, is represented by about 250 ornamental species (Martins et al 1996, Marcon & Costa 2000. It is native to the forests of Central and South America extending from southern Mexico, in the north, toward the south through Guatemala, British Honduras, Nicaragua, Costa Rica, Panama, Colombia, Ecuador, Peru, Bolivia, Brazil, Paraguay, and northern Argentina.…”
Section: Trypanosoma Cruzimentioning
confidence: 99%